2016
DOI: 10.1523/jneurosci.0054-16.2016
|View full text |Cite
|
Sign up to set email alerts
|

Kif1B Interacts with KBP to Promote Axon Elongation by Localizing a Microtubule Regulator to Growth Cones

Abstract: Delivery of proteins and organelles to the growth cone during axon extension relies on anterograde transport by kinesin motors. Though critical for neural circuit development, the mechanisms of cargo-specific anterograde transport during axon extension are only starting to be explored. Cargos of particular importance for axon outgrowth are microtubule modifiers, such as SCG10 (Stathmin-2). SCG10 is expressed solely during axon extension, localized to growth cones, and essential for axon outgrowth; however, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 43 publications
1
28
0
Order By: Relevance
“…Kinesins (KIF proteins) are a large family of microtubule-based intracellular motors that transport cargo from one part of the cell to another. Cell biological approaches revealed that KIF1BP interacts with a subset of kinesins including KIF1A, KIF1B, KIF1C, KIF3A, KIF13B, KIF14, KIF15 and KIF18A 9 11 . Studies using cell lines and zebrafish mutants suggest the main role of KIF1BP is to regulate axon extension.…”
Section: Introductionmentioning
confidence: 99%
“…Kinesins (KIF proteins) are a large family of microtubule-based intracellular motors that transport cargo from one part of the cell to another. Cell biological approaches revealed that KIF1BP interacts with a subset of kinesins including KIF1A, KIF1B, KIF1C, KIF3A, KIF13B, KIF14, KIF15 and KIF18A 9 11 . Studies using cell lines and zebrafish mutants suggest the main role of KIF1BP is to regulate axon extension.…”
Section: Introductionmentioning
confidence: 99%
“…4 D; Fassier et al, 2018). These data suggest that Fignl1 may not be a Kif1bβ cargo, unlike SCG10 (Drerup et al, 2016).…”
Section: Resultsmentioning
confidence: 88%
“…Interestingly, the presence of BICD2 increases the force generation and processivity of dynein/dynactin [127,128], demonstrating that these cargo adapter proteins regulate motor activity and could act as switches to control transport directionality within a complex containing two opposing motors. Other control mechanisms could come from accessory proteins such as kinesin binding protein (KBP), which has been shown to stimulate KIF1B, but inhibit KIF1A mediated bidirec tional transport [28,129]. If the activity of such regulato ry proteins were spatially controlled, this would enable directional switching of transport complexes in the pres ence of opposing motors.…”
Section: Cooperation Of Motorsmentioning
confidence: 99%